Van Homolulu en geheimen : doen en laten van Turks-Nederlandse LHBT's. - van der Klein, Marian; Oostrik, Sven; Duysak, Suna (Utrecht : Kennisplatform Integratie & Samenleving, 2016)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure